Gluconolactone Alleviates Myocardial Ischemia/Reperfusion Injury and Arrhythmias via Activating PKCε/Extracellular Signal-Regulated Kinase Signaling - Qin, Xinghua; Liu, Binghua; Gao, Feng; Hu, Yuanyuan; Chen, Ziwei; Xu, Jie; Zhang, Xing (Frontiers in Physiology, 2022)
Gluconolactone (D-glucono-1,5-lactone or GDL) is a food additive which presents in dietary products such as tofu, yogurt, cheese, bread, wine, etc. GDL has long been considered as a free radical scavenger; however, its role in cardioprotection remains elusive. In this study, using a mouse model of myocardial ischemia/reperfusion (I/R) injury and a model of hypoxia/reoxygenation (H/R) in neonatal rat cardiomyocytes (NRCM), we explored the role of GDL in I/R injury. We found that GDL (5 mg/kg, i.p.) attenuated myocardial I/R injury as evidenced by decreased infarct size, release of cardiac injury markers and apoptosis. Additionally, GDL apparently decreased reperfusion-induced arrhythmias and oxidative stress. These effects were also observed in parallel in vitro studies. Mechanistically, we found that GDL treatment was strongly associated with activation of pro-survival extracellular signal-regulated kinase (ERK) signaling both in vivo and in vitro, and pharmacological inhibition of ERK signaling via U0126 attenuated GDL-induced cardioprotection against H/R injury in NRCM cells. To reveal how GDL regulates ERK signaling, we predicted the putative targets of GDL by Swiss Target Prediction, and protein kinase C (PKC) emerged as the most promising target for GDL. By pharmacological intervention and immunofluorescence, we found that PKCɛ, an important member of the PKC family, was activated after GDL treatment in heart, thereby leading to ERK activation and cardioprotection against I/R injury. Taken together, our results demonstrated that GDL acts as a potent activator of PKCɛ and, thus, provides cardioprotection against I/R injury via activation of ERK signaling.